Manajemen Pembelajaran SKI di MTs Berbasis Meaning Maker dalam Upaya Menghidupkan Makna dan Nilai Sejarah Islam - Dani Muhammad Jalil; Sri Handayani; Eva Dianawati Wasliman (Jurnal Manajemen Pendidikan Islam (MANAPI), 2026)
Islamic Cultural History (SKI) learning in Madrasah Tsanawiyah faces significant challenges, where students experience a crisis of value meaning despite having unlimited access to information. SKI remains trapped in the stigma of being a memorization subject that fails to respond to contemporary students' needs. This study aims to explore SKI learning management based on meaning maker in efforts to bring the meaning and values of Islamic history to life. The research employed Moustakas' transcendental phenomenological qualitative approach with two SKI teachers at MTs Al Fatah, Bandung Regency, as informants. Data were collected through in-depth interviews, classroom observations, and documentation, then analyzed using Moustakas' six stages. The findings reveal three main discoveries: teachers interpret the process of connecting historical narratives with contemporary reality as the core of their professionalism; meaning maker-based learning management strategies include material contextualization, use of reflective questions, and creation of dialogical learning experiences; and teachers demonstrate high pedagogical reflexivity in evaluating their practices. The study concludes that effective SKI learning management requires teacher professionalism encompassing pedagogical competence, managerial capacity, and continuous reflexivity to transform historical narratives into meaningful learning experiences that develop students' transformative historical consciousness